The Efficacy of Therapeutic Use of Play on Improving Attention Span of Mild Intellectually Disabled Children - Tayebeh Pirnazar; Masoumeh Pourmohamadreza-Tajrishi; Ali Zadeh Mohammadi; Milad Haidarian; Ahmad Ahmadi (Iranian Rehabilitation Journal, 2022)
Objectives: This study aimed to determine the efficacy of the therapeutic use of play on improving the attention span of children with Mild Intellectual Disability (MID) in elementary school. Methods: This was a quasi-experimental study with a pre-test-post-test with a control group so that 30 girls with MID were selected from an exceptional school in Tehran City, Iran, via convenience sampling method and assigned to the experimental and control groups. The attention span of all subjects was assessed by the Toulouse-Pieron test and the Cognitive Diagnostic Battery (CDB) before and after the therapeutic sessions. The experimental group participated in 16 therapeutic play sessions (35 minutes for each session) for 8 weeks, but the control group did not. The analysis of covariance (ANCOVA) was used to analyze the data. Results: The mean±SD age were 9.80±1.32 and 9.73±1.22 for the experimental and control groups, respectively. In addition, the mean attention span in the experimental group varied from 7.60 to 18.78 after the therapeutic sessions. In addition, after the therapeutic sessions, a significant difference (P<0.001) was observed between the experimental and control groups relating to attention span. According to the Eta quotient, 94% of the variation in the attention span of the experimental group is due to participating in the intervention sessions. Discussion: Therapeutic use of play is an effective method to improve the attention span of children with MID. Therefore, the therapeutic use of play can be applied to improve the academic performance of students with MID and reduce negative outcomes due to inattention.